Science and practice of strength training - Zatsiorsky, Vladimir M. PhD 1932- (Vladimir Mikhailovich); Fry, Andrew C. PhD 1956-; Kraemer, William J. PhD 1953- (Champaign, IL Human Kinetics, 2021)
"Science and Practice of Strength Training addresses the complexity of strength training programs while providing advice in customizing programs for athletes and other populations. It covers velocity training, intensity, timing, exercises, injury prevention, overtraining, and athlete monitoring"--Provided by publisher
1. Basic concepts of training theory -- 2. Task-specific strength -- 3. Athlete-specific strength -- 4. Training intensity -- 5. Timing in strength training -- 6. Exercises used for training -- 7. Velocity in the weight room -- 8. Injury prevention -- 9. Overreaching, overtraining, and recovery -- 10. Monitoring athletes in the weight room -- 11. Goal-specific strength training -- 12. Strength training for women -- 13. Strength training for young athletes -- 14. Strength training for senior athletes
Recommending faculty - Prof. Niño Ybañez
Includes bibliographical references and index
Keywords: Biomechanics; Muscle strength; Physical education and training